Spatiotemporal Dynamics of Cerebral Vascular Permeability in Type 2 Diabetes-Related Cerebral Microangiopathy - Chen, Ying-Chen; Lu, Bing-Ze; Shu, Yu-Chen; Sun, Yuan-Ting (Frontiers in Endocrinology, 2022)
Aims: Diabetes-related cerebral microangiopathy can manifest as cerebral small vessel disease (CSVD) and exhibit cognitive decline. To find the early change of function in advance, this study examined the spatiotemporal dynamics of cerebral vascular permeability (Ktrans) in the progression of type 2 diabetes mellitus (T2DM). Methods: Ktrans was crossectional measured in T2DM and non-diabetes groups with or without CSVD using dynamic contrast-enhanced MRI (DCE-MRI). Results: In all patients with T2DM, the Ktrans of white matter (WM) was increased, whereas the Ktrans of gray matter (GM) was increased only in T2DM with CSVD. The involvement of WM was earlier than GM and was prior to the CSVD features could be visualized on MRI. Among the commonly available four CSVD items of MRI, microbleeds was most sensitive, indicating the increased permeability in all patients. Increased Ktrans in T2DM was more associated with moderate WM hyperintensity but less with the presence of lacunae or multiple perivascular spaces, in contrast to patients without diabetes. The differential correlation suggested distinct mechanisms underlying diabetes-related CSVD and other CSVDs. Conclusions: This study highlights the early development of cerebral microangiopathy with increased BBB leakage in T2DM, prior to the CSVD features can be visualized on MRI. The results may increase the proactivity of clinicians in recognizing the subsequent neurological comorbidities.